"My father wasn't really interested in machinery": new perspectives on the modernisation of agriculture in 20th century Lincolnshire. (2nd July 2016) - Hunt, Abigail
Abstract : This article explores the emergence of modern agriculture in twentieth century Lincolnshire as represented by the shift from threshing drums to combine harvesters and from real horse power to motor horse power. It attempts to historically resituate the emergence of modern agriculture in the county, demonstrating that change did not uniformly take place across the county just before, during, or immediately after World War Two. It also offers a new perspective on a well-covered historical topic; that of the human experience of modernisation as told by the people who bore witness to a monumental shift in methods of agricultural production.